Faster Graph Traversal Algorithm with Degree Level Ordering - Shyma PV (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Increasing the efficiency of algorithms for fundamental computations can have a wide-ranging impact on the performance of a large number of computations. A search algorithm is one such primitive task, occurring in many systems for identifying the shortest path from the start to the goal. The paper reports a fundamental searching algorithm for traversing a graph with degree level ordering. The adjacency list representation of the graph is used by the algorithm because it is effective in terms of storage and makes it simple to figure out the degree of each node. Without requiring any additional templates, the approach may be applied to both connected and disconnected graphs. The results highlight an efficient graph traversal algorithm and elucidated how the proposed algorithm can be used to solve Maze problem.